Effeminate, Aggressive, and Sexually Dangerous: The Anticlerical Discourse on Spanish Catholic Men (1885-1936) - Camino, Alejandro (Hispania Nova, 2022)
At the end of the 19th century and in the first decades of the 20th century, the Spanish anticlerical sectors developed a double discourse on Catholic men, especially ecclesiastical ones. Catholic men were presented as effeminates, meek, cowards and submissive. At the same time, were defined as sexually dangerous (only the priests, not the pious men), irrationals, and aggressive. Both characterizations were not contradictory. In fact, were complementary. This strategy had the main goal of devaluing the figure of the Catholic man and Catholic masculinity. Besides, it was aimed to warn about the dangers of the ecclesiastical men. The Spanish anticlerical sectors were concern about the priests could control the will of the women of their family. They thought that, if that happened, the priest would be limiting the authority of men as heads of the family.